2020
DOI: 10.3390/genes11040418
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Functional Characterization of a Flavonoid Transport-Related MATE Gene in Asiatic Hybrid Lilies (Lilium spp.)

Abstract: Previous studies have suggested that multidrug and toxic compound extrusion (MATE) proteins might be involved in flavonoid transportation. However, whether MATE proteins are involved in anthocyanin accumulation in Lilium is unclear. Here, a flavonoid transport-related MATE candidate gene, LhDTX35, was cloned from the Asiatic hybrid lily cultivar ‘Tiny Padhye’ by rapid amplification of 5’ and 3’ cDNA ends (RACE) and found to encode 507 amino acids. BLASTx results indicated that LhDTX35 showed high homology to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…GST, acting as a molecules carrier, could mobilizes and transported anthocyanins from the cytoplasm to the tonoplast in the process of synthetic anthocyanin being transport and storage in vacuoles (Sun et al, 2012). Xu et al (2020) verified that the MATE family member DTX35 is related to lily flavonoid transport. Cao et al(2021b)revealed the anthocyanin transport mechanism mediated by GST in lily.…”
Section: Introductionmentioning
confidence: 82%
“…GST, acting as a molecules carrier, could mobilizes and transported anthocyanins from the cytoplasm to the tonoplast in the process of synthetic anthocyanin being transport and storage in vacuoles (Sun et al, 2012). Xu et al (2020) verified that the MATE family member DTX35 is related to lily flavonoid transport. Cao et al(2021b)revealed the anthocyanin transport mechanism mediated by GST in lily.…”
Section: Introductionmentioning
confidence: 82%
“…The findings of previous studies have indicated that anthocyanin transport proteins may play roles in plant vacuoles (Han et al 2022, Pal et al 2023), and PpGST1 , MdGSTF6 , and LcGST4 have been identified as genes encoding proteins associated with the transport of anthocyanins (Hu et al 2016, Jiang et al 2019, Zhao et al 2020). Moreover, LhDTX35 (encoding a MATE) has been established to play a key role in regulating the accumulation of anthocyanins (Xu et al 2020). In the present study, we detected eight GST genes and eight MATE genes characterized by high expression in purple leaves, thereby indicating these genes may be responsible for the transport of anthocyanins during the development of purple leaf coloration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LhDTX35 (encoding a MATE) has been established to play a key role in regulating the accumulation of anthocyanins (Xu et al 2020). In the present study, we detected eight GST genes and eight MATE genes characterized by high expression in purple leaves, thereby indicating these genes may be responsible for the transport F I G U R E 1 1 Heatmap of DEGs in the carotenoid synthesis pathway.…”
Section: Differential Expression Genes Of Carotenoid Synthesismentioning
confidence: 99%
“…is half purple (lower part) and half white (upper part), which is similar to BT flowers. An MATE gene LhDTX35 might function as a carrier protein to transport anthocyanins ( Xu et al, 2020 ). Furthermore, a flavonoid carrier similar to mammalian bilitranslocase (BTL) was identified in grape, and it may participate in long distance transport of flavonoids for its presence in vascular bundles ( Petrussa et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%